PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF MENGGUNAKAN ARTICULATE STORYLINE PADA MATERI KEBERAGAMAN BUDAYA KELAS IV - Jihan Pahira Hidayah; Lina Novita, Ade Wijaya (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The development of this product uses the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The research began with a needs analysis, teacher analysis, student analysis, and product design. The next step was developing the interactive learning media, conducting expert validation, and testing the interactive learning media using Articulate Storyline on the cultural diversity material with the predetermined respondents. The validation results from subject matter experts, language experts, and media experts show that the interactive learning media using Articulate Storyline is highly valid and very feasible for use, achieving an average percentage of 95.5%. In the trial phase, 28 students responded very positively, finding the media highly engaging, with an average score of 84%. Based on these results, it can be concluded that the interactive learning media using Articulate Storyline on the topic of cultural diversity for Grade IV developed in this study is proven to be valid, easy to use, engaging for students, and appropriate for learning.